Vancomycin resistant enterococci colonization in a neonatal intensive care unit: case-control study - Tanyeri-Bayraktar, Bilge; Bayraktar, Suleyman (My University, 2017)
Aim: Vancomycin-resistant enterococcus (VRE) is a concerning microorganism among hospitalized and intensive care patients. The aim of this study was to report the outbreak characteristics, the risk factors, and the outbreak control of VRE colonization in a neonatal intensive care unit and the effect of Lactobacillus reuteri on VRE colonization. Material and Method: Thirty- nine cases and seventy-eight controls were included in the case-control study between December 2012- June 2013. The primary outcome variable was the risk factors of VRE colonization. The secondary outcome was the effect of Lactobacillus reuteri on elimination of VRE. Results: Of 272 neonates, 39 (14.3%) were colonized with VRE. Multivariate analysis suggested that gestational age, shared use of ultrasonography, and receiving anti-methicillin resistant staphylococcus aureus drugs were the risk factors of VRE colonization. Twenty-six of the 39 VRE positive patients received Lactobacillus reuteri. Eleven (42.3%) of 26 patients became negative after the use of probiotics. The clearance time of VRE was 9.61 +/- 5.53 days. Discussion: Low gestational age, shared ultrasonography, and anti- methicillin resistant staphylococcus aureus drug exposure are major independent risk factors for VRE colonization. An effective Infection control programme should be implemented. To determine the effectiveness of probiotics in VRE colonization, further randomized controlled trials must be conducted.